A Study to Evaluate the Effectiveness of Problem Based Learning (PBL) Module on Knowledge and Attitude among Nursing Students. - Gandhi, Srinivasan; Dass, Devan Prabhu (International Journal of Nursing Education)
Objective: To evaluate the knowledge and attitude regarding Problem Based Learning (PBL) Module among Nursing Students, Associate knowledge and attitude scores with selected demographic variables, Correlate the knowledge and attitude of Nursing students who undergone to Problem Based Learning activities. Background: The Problem based learning (PBL) is require for present situation in all aspects of competence care providers and research action tool for upgrading deep knowledge about clinical subjects[1]. Method and Materials: Research approach: Qualitative approach, Research design: Quasi-experimental design. Sampling: The Final year students of B.Sc nursing and GNM whose are final year traing in the clinical area. The Number of students was influenced by the nature of the design and number of respondents. The purposive sampling technique was adopted. It is the participant sense of reality and truth therefore the researcher recruited 40 samples foe the study Results and Discussion: The findings revealed that majority of the students (72.3%) belongs to 18-21 years, 78.2% of the students were from rural background and 21.8% of the students were from urban background. The study revealed that 70.4% of the students had moderately adequate knowledge, 25% had inadequate knowledge and only 4.6 % of nursing students had adequate knowledge in the pretest. The study revealed that 48.8% of the nursing students had adequate knowledge, 6.6% of had inadequate knowledge and only 44.6% of nursing students had moderately adequate knowledge in the posttest. The present study revealed that overall 38.7% of the nursing students had a favourable attitude, 31.7% of the nursing students had moderately favourable attitude and 30 % of nursing students had unfavourable attitude in the pretest. The study revealed that overall 68.5% of the nursing students had favourable attitude, 31.5% of nursing students had moderately attitude in the posttest. There was no significant difference between mean pretest knowledge score (t=1.813,p>0.05).But there was significant difference between mean post-test knowledge score(t=10.814,p>0.05).The results implied that the Problem based learning module was effective sense of performance in improving knowledge among nursing students. There was no significant association between pretest knowledge level among nursing students and age,religion,years and working areas. There was association between pretset levels of knowledge among nursing students regarding Problem based learning module with their source of information. It was found that statistically significant at p>0.05. Conclusion: The nursing students had average knowledge and attitude before planned Problem Based learning module and then the source of information had impact on knowledge and attitude of nursing students. There was no significant association between pre-test knowledge level among nursing students and age, religion, years and working areas. There was association between pre-test levels of knowledge among nursing students regarding Problem based learning module with their source of information. It was found to be statistically significant at P>0.05.